O parágrafo quarto da Octogesima Adveniens e a pastoral político-social - Andrade, Paulo Fernando Carneiro de (Revista Eclesiástica Brasileira, 2009)
Este artigo aborda a questão da relação entre os cristãos e o agir político social sob a ótica da Carta Apostólica Octogesima Adveniens de Paulo VI e do paradigma das relações entre Lei e Moral, presentes no Decreto Conciliar Dignatis Humanae. É grande a atualidade destes dois documentos em um momento em que se torna a discutir as relações possíveis entre religião e política em uma democracia plural e a laicidade do Estado. Quais os limites, possibilidades e exigências para um agir cristão na esfera político-social? Abstract: This article deals with the question of the relation between Christians and the political social action in the light of the Apostolic Letter by Paul VI, Octogesima Adveniens, and of the paradigm of the relations between the Law and Morality, present in the Conciliar Decree Dignatis Humanae. At a time when the discussion of the possible relations between religion and politics in a plural democracy and in a lay State is back on the agenda, the present relevance of these two documents is very great. What are the limits, the possibilities and the demands for the Christian action in the politico-social sphere?